Experimental analysis of continuous steam gasification of wood biomass for syngas production in a high-temperature particle-fed solar reactor - Chuayboon, Srirat; Abanades, Stéphane; Rodat, Sylvain (My University, 2018)
Solar steam gasification of beech wood biomass has been performed in a novel high-temperature continuously-fed solar reactor for the thermochemical conversion of low-grade carbonaceous feedstock into transportable and storable gaseous fuels (syngas). The 1.5 kWth cavity-type solar reactor was operated in the temperature range of 1100–1300 °C. Large wood biomass particles (3–5 mm size) were continuously fed and gasified with the oxidizing agent to produce syngas, thus demonstrating the reactor suitability for large particle size processing. Operating parameters were varied in order to optimize the syngas production. The effect of steam flow-rate, carrier gas flow-rate, temperature, and biomass feeding rate on the syngas yield and reactor performances was experimentally investigated. The increase of steam flow-rate favored H2, CO2 and CH4 and reduced CO production. A noteworthy increase of the syngas yield with the temperature was highlighted, while the increase of carrier gas flow-rate was detrimental to the amount of syngas produced because of lowered gas residence time. The increase of biomass feeding rate (in the range of 0.8–1.8 g/min) showed noteworthy impact on the syngas composition without affecting the reactor performance, yielding high-quality syngas with a carbon conversion rate above 80%, while the total syngas yield was stable at about 70 mmol/gbiomass.
Keywords: Biomass; Concentrated solar energy; Gasification; Solar reactor; Syngas production; Thermochemical conversion